(untitled) (Anclajes, 2022)
We analyze the book Los hongos alucinantes (1964), by Fernando Benítez (1912-2000), through three main approaches: first, as a successor and reformer of the Mexican Indigenista Literature of the 1950s; second, as a border text between literature, journalism and ethnography, in which Benítez "authorizes" himself through specific strategies; third, as a critical text of the anthropological discipline. Strongly influenced by the counterculture of the time and by Literary Indigenismo, Los hongos alucinantes imitates an ethnographic study and creates a border text. His ethnographic immersion and the scriptural strategies used (Clifford Geertz’s “being there”) reveal the “authorization” Benítez employs to legitimize his position.